Psychometric Evaluation of the Czech Version of Group Cohesiveness Scale (GCS) in a Clinical Sample: A Two-Dimensional Model - Klocek, Adam; Řiháček, Tomáš; Cígler, Hynek (Frontiers in Psychology, 2020)
The Group Cohesiveness Scale (GCS, 7 items) measures patient-rated group cohesiveness. The English version of the scale has demonstrated good psychometric properties. This study describes the validation of the Czech version of the GCS. A total of 369 patients participated in the study. Unlike the original study, the ordinal confirmatory factor analysis supported a two-dimensional solution. The analysis demonstrated the existence of two moderately to highly associated (r = .79) domains of group cohesiveness – affective and behavioral. Internal consistency reached satisfactory values for both domains (affective, ω = .86; behavioral, ω = .81). This is the first revision of the factor structure of the GCS in the European context. The scale showed that the Czech version of the GCS is a valid and reliable brief tool for measuring both aspects of group cohesiveness.